Kajian Pengembangan Kawasan Capolaga Sebagai Daya Tarik Ekowisata - Dewi, Yanuarti Kania; Rosyidie, Arief (Center for Research and Community Services ITB, 2008)
The trend of tourist activities has changed in the last ten years, particularly on the awareness about environmental quality, education and involvement of local community. This paper discusses the ecotourism area that has become a tourist attraction as well as environment conservation. Part of ecotourism concept has been applied in the development of Capollaga except for the rest of the areas. Local community has not been intensively involved and has not obtained the optimum benefits from ecotourism in the area. Ecotourism has not contributed much in stimulating the economy of local community as well as of local income. In order to meet the criteria of ecotourism concept, efforts particularly involvement of local community is needed.